Unveiling the reactivity of N-heterocyclic methylene hydrazines - Balayan, Kajal; Biswas, Arindam; Sharma, Himanshu; Tiwari, Prabhakar; Vanka, Kumar; Gonnade, Rajesh G.; Rath, Arup K.; Sen, Sakya S. (Dalton Transactions, 2026)
We present the first reactivity profile of N-heterocyclic methylene hydrazines, revealing distinct competition between steric and electronic control. Reactions with HCl are electronically driven, resulting in protonation at the proximal nitrogen, while the bulky Lewis acid B(C6F5)3 coordinates to the sterically accessible distal nitrogen. Additionally, we demonstrate that these scaffolds undergo spontaneous, base-free HCN elimination with tetracyanoethylene (TCNE) to form highly conjugated molecules with significantly reduced HOMO-LUMO gaps.